Casas conceito, plataforma de projetos avaliação e aplicação da plataforma casas conceito ao programa de moradia econômica da prefeitura de Florida, Uruguay - Cabrera Recoba, Andrés Javier (Premio Internacional de Tesis de Investigación sobre Vivienda y Desarrollo Sustentable 2016. La Vivienda Social Innovación y Tecnología, 2015)
Several social housing programs with different levels of user involvement coexist in Uruguay. Self-management and self-building contribute to the feasibility of these programs and favor the inclusion of a larger number of households. Individual social housing programs offer type plans that allow very little or no growth at all. Prototypes of the Affordable Housing programs implemented by municipal governments have been conceived for large plots and for a single emplacement model: isolated buildings without contact with other constructions. On these grounds −and based on Casas Concepto Plataforma de Proyectos, an academic work developed by a team of the School of Architecture of Universidad de la República, Montevideo, Uruguay (FARQ-UDELAR)− this research introduces the concept of platform as a project strategy and a way of improving the municipal social housing program. The conceptual basis and starting point of this research is the platform as an open operating system in which the house is seen as a process rather than a product. This proposal opposes the prototype-based model as a single and repeatable basic house solution, which is a closed concept leaving few possibilities of customization or expansion as families grow. This work reviews the historical practices of individual and collective production of social housing in Uruguay, mainly from the standpoint of the user as the developer (self-manager, self-builder) of his own dwelling. It also deals with the theory at the origin of the idea of platform as a concept. To this end, housing production in Europe between 1920 and 1970 is evaluated and the application of the concept to Uruguayan University buildings and other examples of implementation in Latin American social housing are analyzed. The rationale and procedures of the Affordable Housing program implemented in the city of Florida (33.640 inhabitants) are examined through specific cases materialized in two different periods: 2010-2013 and 1990-1993. After this analysis, and as the major goal of the research, the implementation of the theory supported by Casas Concepto is evaluated, management and project guidelines are proposed, and a specific tool, the "CC-PVEF Catalog" (a set of programmed growth plans and projects), is developed as a contribution to the program. Finally, progressive housing projects (project + plan) in available plots in the city of Florida are worked out with the CC-PVEF Catalog, for different household scenarios.